Survival Analysis of the Clinical Episodes of Stroke Using Data from Western Delta Region of Nigeria - K. I. Ekerikevwe (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This study is designed to investigate the epidemiology of stroke burden in Western Delta Region of Nigeria. To achieve this, statistical tools were used to analyze and interpret the prevalence of this diseases in the study area- with focus on the medical records (case files) of hundred and twenty-one (221) patients who suffered from stroke and were seen at selected government hospitals in the region, from 2003- 2016. The clinical episodes (CEs) of stroke for the patients who were admitted during acute care period (without discharge against medical advice) and were then assessed for various investigations and treatment interventions and long term care were obtained and statistically studied. The Kaplan-Meier survival estimator shows the survival rate to be 75% in 2003 and 25% in 2016. The year 2009 recorded the highest CEs (28) with survival function (0.23) and 2014 the lowest (4) with survival function (0.11). These have implications for all stakeholders in health matters in the study area. The study recommends an organized effort from both the government and the private sector to tackle the rising stroke burden in Western Delta Region of Nigeria.